Efficacy of double‐scope endoscopic submucosal dissection and long‐term outcomes of endoscopic resection for superficial pharyngeal cancer. Issue 2 (13th September 2016) - Yoshio, Toshiyuki; Tsuchida, Tomohiro; Ishiyama, Akiyoshi; Omae, Masami; Hirasawa, Toshiaki; Yamamoto, Yorimasa; Fujisaki, Junko; Sato, Yukiko; Sasaki, Tohru; Kawabata, Kazuyoshi; Igarashi, Masahiro
Abstract : Background and Aim: Owing to increased awareness and use of narrow‐band imaging, there are more opportunities to treat superficial pharyngeal cancer (SPC). The present study aimed to describe the short‐ and long‐term outcomes of endoscopic resection (ER) for SPC. Methods: This study included 166 consecutive SPC in 113 patients treated during 2006 to 2013 at one referral cancer center. In the first period, we treated patients using endoscopic mucosal resection (EMR), in the second period using conventional ESD (cESD) and in the recent period using double‐scope ESD (dsESD), which involves a second thin endoscope for assistance to produce traction. Median follow‐up period was 30 months. Results: All lesions were diagnosed as squamous cell carcinoma. Complete resection rate of cESD and dsESD procedures was 56.4% and 82.3% ( P < 0.01), and local recurrence rate was 2.6% and 0.0%, respectively. Procedure duration was significantly shorter for dsESD than for cESD ( P < 0.05). Four cases of recurrent lymph node (LN) metastasis were observed; however, all patients with LN metastases survived to a 48‐month median interval after neck dissection. Risk factors for LN metastasis included subepithelium invasion, tumor thickness >1000 μm, droplet infiltration, and lymphovascular invasion. Overall survival rate after 5 years was 79.5%; no patients died of SPC. Cumulative rate of metachronous SPC after 5 years was 46.5%. Conclusion: ER for SPC is a feasible and effective treatment, although metachronous SPC occurred frequently. For the technique of ER, dsESD was effective.